Photocatalytically active ladder polymers. (11th April 2019) - Vogel, Anastasia; Forster, Mark; Wilbraham, Liam; Smith, Charlotte L.; Cowan, Alexander J.; Zwijnenburg, Martijn A.; Sprick, Reiner Sebastian; Cooper, Andrew I.
Abstract : Post-polymerization ladderization is explored as a promising technique to boost the photo-catalytic activity of conjugated polymers. Abstract : Conjugated ladder polymers (cLaPs) are introduced as organic semiconductors for photocatalytic hydrogen evolution from water under sacrificial conditions. Starting from a linear conjugated polymer (cLiP1), two ladder polymers are synthesized via post-polymerization annulation and oxidation techniques to generate rigidified, planarized materials bearing dibenzo[ b, d ]thiophene (cLaP1) and dibenzo[ b, d ]thiophene sulfone subunits (cLaP2). The high photocatalytic activity of cLaP1 (1307 μmol h −1 g −1 ) in comparison to that of cLaP2 (18 μmol h −1 g −1 ) under broadband illumination ( λ > 295 nm) in the presence of a hole-scavenger is attributed to a higher yield of long-lived charges (μs to ms timescale), as evidenced by transient absorption spectroscopy. Additionally, cLaP1 has a larger overpotential for proton reduction and thus an increased driving force for the evolution of hydrogen under sacrificial conditions.